Effect of anatomical variability on stress‐shielding induced by short calcar‐guided stems: Automated finite element analysis of 90 femora. Issue 3 (28th February 2019) - Sas, Amelie; Pellikaan, Pim; Kolk, Sjoerd; Marty, Pablo; Scheerlinck, Thierry; van Lenthe, G. Harry
ABSTRACT: Short stem hip implants are becoming increasingly popular since they preserve bone stock and presumably reduce stress‐shielding. However, concerns remain whether they are suitable for a wide range of patients with varying anatomy. The aim of this study was to investigate how femoral anatomy influences stress‐shielding induced by a short calcar‐guided stem across a set of 90 CT‐based femur models. A computational tool was developed that automatically selected the optimal size and position of the stem. Finite element models of the intact and implanted femurs were constructed and subjected to walking loads. Stress‐shielding was evaluated in relevant volumes of interest of the proximal femur. After a detailed anatomical analysis, linear regression was performed to find potential correlations between anatomy and stress‐shielding. Stress‐shielding was found to be highest in the proximal regions on the medial and posterior side. A highly significant negative relationship was observed between stress‐shielding and bone density; a strong positive relationship was observed with stem size and the valgus orientation of the stem with respect to the femur. The results reveal how anatomy influences stress‐shielding, and they highlight the importance of evaluating new implant designs across a large population taking into account the anatomical variability. The study demonstrates that such large population studies can be conducted in an efficient way using an automated workflow. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:1–8, 2019.